The Descriptive Study of Applying the English Day in Improving the Secondary Boarding School Students’ Speaking Ability - Muzakki, M.; Basya, Dihliza (Linguapedia, 2022)
English Day is one of the development programs and language training conducted in one of the Islamic boarding schools in Jember with the intention of achieving maximal learning English speaking, especially in achieving the ability to speak English fluently. For this reason, this qualitative research is aimed to provide a rich, contextualized picture of English Language Day in one of the Islamic Boarding School in Jember, Indonesia (according to Denzin & Lincoln, Schwandt on Donna M. M and John A.M, 2004:95). By employing observation, documentation, and interview the data showed that although English Day is a good method for students to practice their English ability, some students still show inadequacy to speak English fluently.